ANALISIS KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV SEKOLAH DASAR PADA MASA PANDEMI COVID-19 - Nur Anisa Fitri Hasan, - (2021)
the background of this research is fourth grade students who are low in reading comprehension skills during the covid-19 pandemic. The purpose of this research is to see the students' reading comprehension ability, the factors causing the low reading comprehension ability, and the solutions that can be used to overcome the low reading comprehension ability of the fourth grade students of MI Nahdlatul Athfal. The research method used in this research is case study analysis with 3 fourth grade students as research subjects. Data collection methods are tests, documentation, observation, and interviews. The results of this study indicate that there are two categories of reading comprehension skills, namely the able and not able categories. Factors causing the low reading comprehension of grade IV students during the covid-19 pandemic, namely reading atmosphere, reading atmosphere that is not conducive, And an uncomfortable atmosphere that makes students bored and makes students' concentration disturbed, does not have infrastructure that supports students to stay calm, limited reading books, uses words that are difficult for students to understand, lacks attention to reading details so that it triggers difficulty understanding the contents of the reading. The solution that can be applied by parents, teachers and students at home is using the Directed Reading Thinking Activity (DRTA) strategy.